The effect of education on fertility: Evidence from a compulsory schooling reform - Kamila Cygan-Rehm; Miriam Maeder (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
This paper investigates the effect of education on fertility under inflexible labor market conditions. We exploit exogenous variation from a German compulsory schooling reform to deal with the endogeneity of education. By using data from two complementary data sets, we examine different fertility outcomes over the life cycle. In contrast to evidence for other developed countries, we find that increased education causally reduces completed fertility. This negative effect operates through a postponement of first births away from teenage years, and no catch-up later in life. We attribute these findings to the particularly high opportunity costs of child-rearing in Germany.
Keywords: I21; J13; J24; 330; fertility; education; childlessness; timing of births; educational reform